How kebud: back to roots programme affects volunteers’ perceptions and appreciation towards cultural arts performances - Nur Syazana Seruji,; Mohamad Iqwan Roslanni,; Nur Husnina Mohamad Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Volunteerism has always been synonymous with giving back to society. According to Bjalkebring et. al (2020) volunteering is considered a prosocial behaviour which is a behaviour that benefits society. Next, we must consider the potential factors that influence students’ recognition of cultural arts. The main objective of this study is to establish the future relationship between cultural performing arts and volunteerism. The second objective of this study is to accelerate students' growth and help them become part of a high-functioning society that integrates volunteerism in managing and organizing cultural arts performances. The third objective is to showcase the potential of Malaysia as a developing country that places cultural heritage as its core speciality. The motivation for volunteering is based on personal values towards oneself and society for the sake of their country (Moore et. al, 1996). "Hersberger-Langloh et al. (2010) hypothesized that students volunteer for cultural arts performances either because they enjoy the activity itself or the outcomes it produces. This involvement not only enhances the students' appreciation of the arts but also enables them to influence and encourage other communities to value these cultural performances. The impact of the study is that it enables the community to conduct more volunteering activities that contribute to all cultural arts performances in Malaysia.